2017
DOI: 10.1002/2017jc012966
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Decay Mechanisms of Ningaloo Niño/Niña

Abstract: Using an ocean model, generation and decay mechanisms of warm/cool sea surface temperature anomalies (SSTAs) off Western Australia, or Ningaloo Niño/Niña, are investigated through the calculation of a mixed‐layer temperature (MLT) balance taking the mixed‐layer depth (MLD) variation into account. Since Ningaloo Niño/Niña develops owing to local air‐sea interaction and/or remote forcing, events are classified into two cases based on alongshore wind anomalies and analyzed separately. It is revealed that the anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 33 publications
4
68
1
Order By: Relevance
“…The absence of ENSO in austral spring could offer favorable conditions for local SST forcing because La Niña tends to suppress the atmospheric convection off Western Australia (supporting information Figure S7) and thus, may explain the difference in the amplitude of Ningaloo Niño between the CTRL and noENSO experiment. We note that while latent heat loss is reduced over the offshore region (supporting information Figure S6), which also favors shallower MLD, its direct warming effect is offset by the enhanced cooling by the climatological latent heat flux according to Kataoka et al ().…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…The absence of ENSO in austral spring could offer favorable conditions for local SST forcing because La Niña tends to suppress the atmospheric convection off Western Australia (supporting information Figure S7) and thus, may explain the difference in the amplitude of Ningaloo Niño between the CTRL and noENSO experiment. We note that while latent heat loss is reduced over the offshore region (supporting information Figure S6), which also favors shallower MLD, its direct warming effect is offset by the enhanced cooling by the climatological latent heat flux according to Kataoka et al ().…”
Section: Resultsmentioning
confidence: 65%
“…We performed two CGCM experiments and demonstrated that in the noENSO sensitivity experiment, Ningaloo Niño/Niña develops even without ENSO with a similar amplitude, duration, and seasonality. The driving mechanism seems to be the intrinsic air‐sea interaction off the west coast of Australia shown in earlier studies (e.g., Kataoka et al, , ; Tozuka et al, ), which can amplify initial atmospheric or oceanic perturbations. In this positive air‐sea feedback, a local warm SST anomaly would strengthen atmospheric deep convection to the northwest of Australia, which is accompanied by low SLP anomalies off Western Australia, northwesterlies extending westward of the convection anomaly, and alongshore‐northerly wind anomalies (Matsuno‐Gill response).…”
Section: Conclusion and Discussionmentioning
confidence: 85%
See 3 more Smart Citations